2011
DOI: 10.1088/0967-3334/32/8/007
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation and testing of an implantable impedance-based feedback-controlled neural gastric stimulator

Abstract: Functional neural gastrointestinal electrical stimulation (NGES) is a methodology of gastric electrical stimulation that can be applied as a possible treatment for disorders such as obesity and gastroparesis. NGES is capable of generating strong lumen-occluding local contractions that can produce retrograde or antegrade movement of gastric content. A feedback-controlled implantable NGES system has been designed, implemented and tested both in laboratory conditions and in an acute animal setting. The feedback s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Oscillator: Previous literature demonstrated that 50 kHz is an optimal frequency for luminal electrical impedance measurements to minimize interference with regular muscle, nerve, and organ functions, while enabling effective transmission through the body[26,27]. Body conduction of small low frequency signals has been clinically proven to be safe, and has found application in other GI related technologies[29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillator: Previous literature demonstrated that 50 kHz is an optimal frequency for luminal electrical impedance measurements to minimize interference with regular muscle, nerve, and organ functions, while enabling effective transmission through the body[26,27]. Body conduction of small low frequency signals has been clinically proven to be safe, and has found application in other GI related technologies[29].…”
Section: Methodsmentioning
confidence: 99%
“…It has been already discussed that the intrinsic gastric electrical oscillator is a complex, multicomponent and dynamic phenomenon, whose relationship with actual gastric motility is so multifaceted that plain EGG cannot reliably assess it. Thus, we recently proposed to enhance an ingestible pill containing a temporary, controllable pseudobezoar with a miniature electronic oscillator of known and strong enough emitting frequency, optimized for good transluminal transmission[26-28]. This is a way to essentially enhance the intrinsic gastric electrical oscillator with a strong, simple, single-frequency source, which could be easily detected cutaneously by traditional EGG equipment and can be consequently processed by the same signal processing tools that plain EGG testing of today employs.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement lasted for more than one week and the threshold became 5.82 g on day 14. In the second PRF stimulation on day 14, the threshold was still improved but reached a high of 9.08 g on day 15. The efficacy decreased and the effective period became short.…”
Section: B Von Frey Testmentioning
confidence: 96%
“…The is equal to the reflected resistance defined in (15). From (13), the input reactance is also mixed with the reactance of .…”
Section: B Measuring Inductive Coupling Impedancementioning
confidence: 99%
See 1 more Smart Citation